Moving Romans : migration to Rome in the principate - Tacoma, Laurens Ernst (Oxford University Press, 2016)
'Moving Romans' provides a coherent framework for the study of Roman migration on the basis of a detailed study of migration to the city of Rome in the first two centuries A.D. It shows how migration influenced other aspects of Roman society, including social relations, the family, work, and cultural interaction